STUDIES ON ARSENICAL CREOSOTE AS A WOOD PRESERVATIVE FOR MARINE STRUCTURE- PART II-OBSERVATION ON LEACHING CORROSIN AND RESISTANCE TO BORER ATTACK - NAIR, N, "UNNIKRISHNAN; PILLAI, A. G. GOPALAKRISHNA; BALASUBRAMANYAN, R (Fishery Technology, 2016)
A detailed study on arsenical creosote with reference to leaching, corrosion and anti-borer p-roperties was carried out, Results showed that aging had vety little effect on the preservative which suggested better fixation of the preservative into the wood. Corrosion of mild steel, galvanised iron, aluminium-magnesium alloy (M57S) and copper panels in the preservative was found to be negligible, Normal creosote and low temperatme creosote of Regional Research Laboratory, Hyderctbad, both fortified with arsenic trio:xjde resisted borer damage on wooden pands for a period of over five months in the port of Cochin. The perfor-mance of low temperature creos.ote fortified with arsenic was found to be equally satisfactory when compared to normal creosote for-tified in the same manneL A loading of 208.6 Kgsjml> for Haldtt (Adina cordifolia) and 138 Kgsjm’Â§ for Mango (lvfangifera indica) in the case of normal creosote and 177 Kgs/m :e. for Mango the case of RRL creosote were found to be su.fficient for treating the wood.